114 Evaluation of Selenium Source on Nursery Pig Growth Performance, Serum and Tissue Selenium Concentrations, and Serum Antioxidant Status. (12th April 2022) - Rao, Zhong-Xing; Tokach, Mike D; Woodworth, Jason C; DeRouchey, Joel M; Goodband, Robert D; Gebhardt, Jordan T
Abstract: A total of 3, 888 pigs (337×1050, PIC, Hendersonville, TN; 6.0 kg at weaning) were used in a 42-d study to determine the influence of Se source on nursery pig selenium status and growth performance. At placement, pens of pigs were weighed and allotted to 1 of 3 dietary treatments in a randomized complete block design with blocking structure including sow farm origin, date of entry, and average pen BW. A total of 144 pens were used with 72 double-sided 5-hole stainless steel, fence-line feeders, with feeder serving as the experimental unit. For each feeder, 1 pen contained 27 gilts and the other 27 barrows. There were 24 replicates per treatment. Diets were fed in 3 phases, and all contained 0.3 ppm added Se. A common phase 1 diet contained added Se from sodium selenite and was fed in pelleted form to all pigs for 7 d prior to initiation of treatment diets. Three Se sources [sodium selenite; Se yeast; and hydroxy-selenomethionine (OH-SeMet)] were used to formulate 3 experimental treatments in meal form for phase 2 (d 7 to 21) and phase 3 (d 21 to 42). During the common phase 1 period, ADFI tended ( P < 0.10) to be different (107, 103, and 102 g/d) for sodium selenite, Se yeast, and OH-SeMet, respectively. From d 7 to 42 (treatment period), pigs fed OH-SeMet tended to have decreased ADG ( P < 0.10) and had increased ( P < 0.05) serum, liver, and muscle selenium concentration compared with other treatments. There was no difference ( P > 0.05) in antioxidant status as measured by serum GSH-Px or TBARS. In summary, compared with sodium selenite and selenium yeast, OH-SeMet had greater bioavailability as indicated by increased serum and tissue selenium concentration; however, antioxidant status was similar between treatments and OH-SeMet tended to reduce growth performance compared with pigs fed sodium selenite.